Financial Inputs for Ecosystem Service Outputs: Beach Recreation Recovery After Investments in Ecological Restoration - Pouso, Sarai; Ferrini, Silvia; Turner, R. Kerry; Uyarra, María C.; Borja, Ángel (Frontiers in Marine Science, 2018)
In the Nerbioi estuary (North Spain), the Wastewater Treatment Plant (WWTP) constructed in 1990 resulted in an abrupt decrease in water pollution and an opportunity for improved recreational experiences in the three beaches on the estuary. The monetary value of these recreational benefits was estimated using the travel cost method and compared, via a partial cost-benefit analysis, with the costs of beach maintenance. The travel cost models reveal that summer recreational trips to the three Nerbioi beaches have a value of 5.99, 7.06, and 8.09 € trip-1, respectively. Visitor’s profile and social characteristics influenced the models, while the effects of these variables also varied across beaches. Following a conservative approach, the aggregate recreational value of the estuarine beaches was estimated to be more than 3.5 million year-1. This economic benefit, obtained from summer estimates and focusing on one ecosystem service (i.e., beach recreation) from the multiple ones offered by the estuary, is sufficient to cover 100% of annual beach maintenance costs and 12% of the annual sewerage system running costs. Our findings highlight that investing in water sanitation projects such as WWTPs are not only important for the ecological recovery of degraded coastal environments, but also produce additional human benefits that are able to cover (at least) part of the running cost of these large capital investments.